Evaluasi Sistem Pendidikan Multikultural dalam Pengembangan Diri Peserta Didik di SMP Negeri 1 Kota Gorontalo - Manti S Bempa; Asiah T Pido (Pascasarjana IAIN Sultan Amai Gorontalo, 2020)
Multicultural education offers alternatives through strategic applications and educational concepts based on the use of diversity in people's lives, especially students, such as ethnic, cultural, linguistic, religious, and racial diversity. This study aims to describe the evaluation steps of the multicultural education system in the self-development of students in junior high schools Negeri 1 Gorontalo City. The method used is a qualitative approach, with observation and interview techniques. The results showed that the steps in evaluating the multicultural education system in student self development used the Countenance Stake evaluation model approach: 1) The initial steps focus on the symptoms or phenomena that were evaluated according to the K'13 Revised 2017; 2) Collect information based on the characteristics of basic competencies in KI-1 and KI-2; 3) Entering the description data in the matrix framework in this case using the assessment format; 4) Process data analysis on a matrix framework using assessment standards; and 5) Make a report about the results of the analysis